2020
DOI: 10.1088/2515-7647/ab8a5a
|View full text |Cite
|
Sign up to set email alerts
|

Low-dimensional materials as saturable absorbers for pulsed waveguide lasers

Abstract: Low-dimensional (LD) materials, such as 2D materials, carbon nanotubes, and nanoparticles, have attracted increasing attention for light modulation in photonics and optoelectronics. The high nonlinearity, broad bandwidth, and fast response enabled by LD materials are critical to realize desired functionalities in highly integrated photonic systems. Driven by the growing demand for compact laser sources, LD materials have recently demonstrated their great capacity as saturable absorbers in pulsed (Q-switched or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 159 publications
(139 reference statements)
0
5
0
Order By: Relevance
“…Low-dimensional nanocarbons such as graphene and carbon nanotubes have been successfully recognized as suitable SAs in Q-switched [17][18][19][20][21] and mode-locked Yb 3+ -doped fs-DLW WG lasers. [22][23][24][25] They exhibit superior optical properties including ultra-broadband nonlinear absorption, large nonlinearity and ultrafast relaxation time, and enable a relatively low cost and facile fabrication process. [26,27] In addition, they possess a high level of robustness and chemical (environmental) stability compared with other nanomaterials.…”
Section: Introductionmentioning
confidence: 99%
“…Low-dimensional nanocarbons such as graphene and carbon nanotubes have been successfully recognized as suitable SAs in Q-switched [17][18][19][20][21] and mode-locked Yb 3+ -doped fs-DLW WG lasers. [22][23][24][25] They exhibit superior optical properties including ultra-broadband nonlinear absorption, large nonlinearity and ultrafast relaxation time, and enable a relatively low cost and facile fabrication process. [26,27] In addition, they possess a high level of robustness and chemical (environmental) stability compared with other nanomaterials.…”
Section: Introductionmentioning
confidence: 99%
“…, which allows us to simulate the optical response at varying intensities of light. This model is applicable to many saturable absorbing materials, including quantum dots [18], rare-earth ions [19], and low dimensional materials [20]. The response of the saturable absorbers to an incident electric field is described by the Maxwell Bloch equations [21], which allow us to calculate 𝜒 !"…”
Section: Saturable Absorber Modelmentioning
confidence: 99%
“…[ 35 ] Li et al reviewed recent advances in pulsed waveguide lasers based on low‐dimensional materials. [ 36 ] Kuznetsov et al reported preparing MoSe 2 , NiO, VO 2 , Bi 2 Se 3 , Bi 2 Te 3 , and Sb 2 Te 3 nanolayers using MOCVD technology. The transition from CW to Q‐switch mode is realized for several samples with taper diameters less than 11 µm.…”
Section: Introductionmentioning
confidence: 99%